2019
DOI: 10.1101/680991
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

miR-92a-3p controls cell cycle progression in zebrafish

Abstract: Biological functions of micro RNAs (miRNAs) in the early stages of vertebrate development remain largely unknown. In zebrafish, miRNA miR-92a-3p is abundant in the germ cells throughout gonadal development, as well as in ovulated oocytes. Previously, we demonstrated that inhibition of miR-92a-3p in mature ovaries resulted in developmental arrest at the 1-cell stage upon fertilization of the affected oocytes. This suggested functions of miR-92a-3p in early development. In the present study, we identified wee2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…1 C) that showed those miRNAs that were constitutively differentially expressed between both sexes.
Figure 1 The number of miRNAs that were significantly expressed (average normalized reads > 100) of two AB strains (current data and Desvignes et al 18 ) and zf45Tg hybrid zebrafish (Presslauer et al 47 ). ( A ) In ovaries, and ( B ) testes.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 C) that showed those miRNAs that were constitutively differentially expressed between both sexes.
Figure 1 The number of miRNAs that were significantly expressed (average normalized reads > 100) of two AB strains (current data and Desvignes et al 18 ) and zf45Tg hybrid zebrafish (Presslauer et al 47 ). ( A ) In ovaries, and ( B ) testes.
…”
Section: Resultsmentioning
confidence: 99%
“…Another miRNA that was upregulated by heat treatment was dre-miR-92a, which has been found as the most abundant miRNA in zebrafish gonads 17 . This miRNA was responsible for cell cycle progression during the early stage of embryo development and metamorphosis in both Japanese flounder ( Paralichthys olivaceus ) 46 and in zebrafish 47 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has demonstrated that during the early stages of embryogenesis of D. rerio , maternal miR-92a-3p can suppress the cyclin dependent kinase 1 inhibitor (Wee 1 homolog 2), which regulates cell cycle progression. A significantly higher rate of embryonic developmental arrest at the one-cell embryo stage was observed due to the inhibition of maternal miR-92a-3p expression 38 . let-7 is one of the miRNAs family initially identified in Caenorhabditis elegans as a key developmental switch and plays a crucial role in controlling the transition from larva to adult 39 .…”
Section: Discussionmentioning
confidence: 94%
“…miR‐92a‐3p is a maternal transcript housed in unfertilized eggs that acts as a suppressor of wee2 , a cyclin‐dependent kinase 1 inhibitor, consequently promoting the progression of cell cycle during early embryogenesis in zebrafish (Presslauer et al . 2019). While high expression of miR‐430‐3p and miR‐22a‐3p was unique in ovary, testicular abundance of miR‐125c‐5p and miR‐462‐5p was noted (Presslauer et al .…”
Section: Zebrafish (Danio Rerio)mentioning
confidence: 99%